Adsorptive separation of Cu(II) ions from aqueous medium using thermally/chemically treated Cassia fistula based biochar. (10th March 2020) - Hemavathy, R.V.; Kumar, P. Senthil; Kanmani, K.; Jahnavi, N.
Abstract: The present study demonstrates the adsorption of Cu(II) ions by Cassia fistula seed derived biochar materials. The activation and surface modification were done by pyrolysis and chemical bath in a different acidic medium. The quality of the prepared adsorptive materials was analysed using different analytical techniques. An appropriate surface characteristic was observed which mediates the adsorptive removal. The possible operating conditions for Cu(II) removal is as follows: pH = 5.0; Cu(II) ion concentration at initial = 50–200 mg/L; adsorbent dose = 2.5 (Hydrochloric acid treated Cassia fistula biochar, HTCF), 1.5 (Physically treated Cassia fistula biochar, PTCF) and 0.6 g/L (Sulphuric acid treated Cassia fistula biochar, STCF); temperature = 303 K; time of contact = 30 min. Among various adsorption equilibrium models, Redlich-Peterson and Freundlich models exhibited best fit (R 2 > 0.99) to the adsorption equilibrium data. Langmuir adsorption capacities of HTCF, PTCF and STCF have been found as 72.9, 115.4 and 303.5 mg/g respectively. The adsorption process was exothermic and spontaneous resulted from the thermodynamic analysis. Pseudo first-order best fits the kinetic data with higher correlation coefficient and low error values. Overall, STCF can be a viable option for the commercial adsorbents to treat the industrial wastewater. Graphical abstract: Image 1 Highlights: Cassia fistula seed based biochar materials have been prepared. Biochar materials have been effectively applied for copper removal from aqueous solution. Langmuir biosorption capacity of Sulphuric acid treated Cassia fistula biochar was found to be of 303.5 mg/g. Freundlich and pseudo-first order models best obeyed with studied system. The experimented adsorption system was found to be feasible, spontaneous and exothermic.